Pendampingan belajar operasi hitung menggunakan metode bersusun - Wahyuni, Nurul; Husna, Raudatul (Al-Azkiya: Jurnal Pendidikan MI/SD, 2023)
The use of the stacking method can improve students' abilities and make it easier for students to do multiplication calculation operations. The purpose of this community service activity is to increase students' assistance in completing integer multiplication calculation operations using the stacking method so that students can easily understand the material presented. Based on the assistance activities that have been carried out during the service activities, the results obtained those students can more easily understand multiplication by using the stacking method, the stacking method is proven to increase students' interest in learning to solve multiplication materials, and students can solve multiplication problems in a relatively faster time. Thus, it is proven that the stacking method is very effective to be used as an alternative to learning multiplication.